INVESTIGATION OF NITROGEN AND PHOSPHORUS CONTENT IN ARABLE AGRICULTURAL LAND IN SERBIA - Simić, Divna; Janković, Snežana; Popović, Vera; Ikanović, Jela; Stanković, Sladjan; Rakić, Sveto; Stevanović, Petar (Journal of Agricultural Sciences (Belgrade), 2023)
The aim of this study was to determine the content of nitrogen and phosphorus in the soil of Serbia, in the territory covered by the work of the Agricultural Advisory and Expert Services of Central Serbia (PSSS). The study includes data on the content of nitrogen and phosphorus in arable agricultural land based on the soil fertility control conducted by PSSS in 2020. Fertility control was done with digital records of sampling and a software platform for providing advice on the use of fertilizers and other measures to preserve soil quality. Chemical analysis of the samples was done at accredited laboratories. Nitrogen (N) content was determined by using the Kotzman method and calculated from humus, on a sample of 30,957 plots comprising the area of 19,629.24 ha. Phosphorus content (P2O5) was determined according to the method of Engenr and Riehm, on a sample of 28,944 plots comprising the area of 18.459,96 ha. The obtained results showed that 64.59% of the areas, i.e. 12.678,81 ha, had a good level of nitrogen (0.2-0.1%). On about 27.68% of the areas, which is 5.108,92 ha, a very high level of phosphorus was determined (40.01-50.00 mg/100g of soil). The obtained results contribute to the development of chemical application strategies and environmental sustainability without toxicity, i.e. a fair, healthy and environmentally-friendly food production system. [1]* Autor za kontakt: e-mail: dsimic@ipn.co.rs [2]* Corresponding author: e-mail: dsimic@ipn.co.rs